Mengungkap Pengalaman Pribadi melalui Metode Narasi Oral pada Penelitian Bidang Pendidikan - Yurni Yurni (Jurnal Ilmiah Dikdaya, 2023)
The use of the oral narrative method in research is not something new. This method has been used for quite a long time, especially in the fields of psychology, sociology and education research. In the field of education, oral narrative methods are used to express educational experiences through telling stories about an individual or a group of people so as to make the stories depicted come true. The general concept underlying this method is that education and educational research are the construction and reconstruction of personal and social stories, where learners, teachers, and researchers are people who are able to tell stories and characters from their own stories. This study discusses the methods and ways of applying oral narratives in the field of education.